Prospects of Neutralizing Nanobodies Against SARS-CoV-2 - Chen, Fangfang; Liu, Zhihong; Jiang, Fan (Frontiers in Immunology, 2021)
Since December 2019, the SARS-CoV-2 has erupted on a large scale worldwide and spread rapidly. Passive immunization of antibody-related molecules provides opportunities for prevention and treatment of high-risk patients and children. Nanobodies have many strong physical and chemical properties. They can be atomized, administered by inhalation, and can be directly applied to the infected site, with fast onset, high local drug concentration/high bioavailability, and high patient compliance (no needles). It has very attractive potential in the treatment of respiratory viruses. Rapid and low-cost development of nanobody targeting SARS-CoV-2 can quickly be developed. Nanobodies against SARS-CoV-2 mutant strains also can be utilized quickly to prevent the virus from escaping. It provides important technical supports for the treatment of the SARS-CoV-2 and has the potential to become an essential medicine in the toolbox against the SARS-CoV-2.